Avaliação dos impactos econômicos e sociais da tecnologia trio da produtividade na cultura da mandioca no município de Moju - SILVA, Daniel da Fonseca (Universidade Federal do Pará, 2018)
This research has been focused to evaluate the economic and social impacts from the technology’s adoption named “Trio da Produtividade” (generated Embrapa Amazônia Oriental) for the cassava crops in the city of Moju/PA. The “Trio da produtividade” is the combination of three components in the system for cassava’s production: (i) selection of manioc stem; (ii) spacing of 1 m x 1 m and (iii) weeding in the first 150 days. This analysis was carried out from the primary data collection, by means of technical panels, producers ́ interviews, advisory officers and municipal and state secretaries ́ of agriculture and the environment, and bibliographical survey. It was found that the “Trio da Produtividade” has brought economic and social impacts positive. The economic impacts was found that: (i) in terms of the root, the “Trio da Produtividade” brought an increase of 7 tons/hectare; (ii) the use of technology provides a net income per hectare of R$ 2,260.00 (61.31 % greater); (iii) about the economic feasibility, the “Trio” proved to be superior in indicators VPL, TIR, rate of return, and suffix of profitability, the production system traditionally used by farmers in the city of Moju. Regarding the social impacts, it was found that the technology showed additional benefits in relation to the traditional system, with positive values of 1.80 . In addition, the effect of the increase of production, that is reflected in higher income generation, food security and employment opportunity to relatives and local workers. The workers ́ participation in trainings on the technology’s application brings a breakthrough in the qualification of the workforce, which allows additional remuneration for the differentiation of them. It was also observed, expectation of improvement management of activity by the producers, because the training for participating and greater dedication to activity.